Early growth decisions of entrepreneurs: The influence of competency and prior performance under changing market conditions - Mullins, John W (Journal of Business Venturing, 1996)
The transition between the founding of firms and their first steps toward growth represents a critical juncture in the life cycle of new firms. An experimental study was conducted among a sample of 103 owner-operators of independent hardware stores, in order to examine the effects of their competency and their store's prior performance on their decisions to grow their business under changing market conditions. The results of the study indicate that prompt and vigorous actions to grow the business in response to market changes are more likely under the following conditions: A high level of competence in the firm combined with poor prior performanceA low level of competence in the firm, combined with good prior performance These findings attest to the critical importance of competency building in new and small firms, as competency appears to facilitate responsive behavior to changing market conditions when the firm's performance has not been favorable. Such competencies may go beyond technical competencies and may include the ability of firms to build relationships with current and prospective customers, which may help the firm anticipate and better understand customer needs. The results also indicate that the folklore about the vigorous responsiveness of entrepreneurs across all kinds of situations, and in the face of all sorts of adversity, may be misplaced or inaccurate. The varying patterns of responsiveness found in our study should provide food for thought, particularly for entrepreneurs who are fortunate to find themselves in positions in which the firm's competencies are high and its prior performance good. Under such circumstances, our results show that a “fat cat” syndrome is likely to set in and undermine the responsiveness of the firm to changing market conditions. For public policy-makers, our results suggest that programs which support competence-building among entrepreneurs whose firms are struggling may play an important role in assisting them to respond to the changes they so frequently face in today's markets. Such programs, which may enhance survival rates of firms already in existence as well as encourage them to grow, may aid in job creation and in maintaining a robust economic environment.